Avoiding radial nerve palsy in proximal radius shaft plating – a cadaver study. (November 2017) - Schwarz, Angelika M.; Hohenberger, Gloria M.; Weiglein, Andreas H.; Riedl, Regina; Staresinic, Mario; Grechenig, Stephan
Abstract: Background: Opinions vary concerning the position of forearm rotation during detachment of the supinator in radial nerve palsy Henry's and Thompson's approaches. Purpose: To define the optimal forearm position for a safe detachment of the supinator during these approaches and to clarify their close relationship to the posterior interosseous nerve (PIN). Methods: The study sample comprised 90 upper extremities of 45 human adult cadavers, embalmed using Thiel's method. After detection of the radial nerve in the interval between the brachialis and brachioradialis, its pathway was traced to the Arcade of Frohse (AF). Measurements involved the distance between the AFand the radial border of the distal biceps tendon (DBT) in pronation and supination, the interval between the AF and the radiocapitellar joint space (RCJS) in supination and the radial length (RL). Results: Distances between the DBT and the AF were significantly shorter during pronation (right side: 14.1 ± 3.4 mm; left side: 13.5 ± 3.2 mm) compared with supination (right side: 20.5 ± 3.6 mm; left side: 19.8 ± 3.5 mm) for both right and left extremities. The mean interval between the AF and the centre of the RCJS was 25.2 ± 5.9 mm for the right side and 24.7 ± 5.6 mm for the left side, which correlated positively with the RL. Conclusion: These results indicate a safe detachment of the supinator from the radius with the forearm placed in supination during both Henry's and Thompson's approaches.